Achievable Benchmarks of Care for Pediatric Readmissions. Issue 9 (10th May 2019) - Montalbano, Amanda; Quiñonez, Ricardo A; Hall, Matt; Morse, Rustin; Ishman, Stacey L; Antoon, James W; Gold, Jessica; Teufel, Ronald J; MD, Vineeta Mittal; Shah, Samir S; Parikh, Kavita
Abstract : BACKGROUND: Most inpatient care for children occurs outside tertiary children's hospitals, yet these facilities often dictate quality metrics. Our objective was to calculate the mean readmission rates and the Achievable Benchmarks of Care (ABCs) for pediatric diagnoses by different hospital types: metropolitan teaching, metropolitan nonteaching, and nonmetropolitan hospitals. METHODS: We used a cross‐sectional retrospective study of 30‐day, all‐cause, same‐hospital readmission of patients less than 18 years old using the 2014 Healthcare Utilization Project National Readmission Database. For each hospital type, we calculated the mean readmission rates and corresponding ABCs for the 17 most common readmission diagnoses. We define outlier as any hospital whose readmission rate fell outside the 95% CI for an ABC within their hospital type. RESULTS: We analyzed 690, 949 discharges at 525 metropolitan teaching hospitals (550, 039 discharges), 552 metropolitan nonteaching hospitals (97, 207 discharges), and 587 nonmetropolitan hospitals (43, 703 discharges). Variation in readmission rates existed among hospital types; however, sickle cell disease (SCD) had the highest readmission rate and ABC across all hospital types: metropolitan teaching hospitals 15.7% (ABC 7.0%), metropolitan nonteaching 14.7% (ABC 2.6%), and nonmetropolitan 12.8% (ABC not calculated). For diagnoses in which ABCs were available, outliers were prominent in bipolar disorders, major depressive disorders, and SCD. CONCLUSIONS: ABCs based on hospital type may serve as a better metric to explain case‐mix variation among different hospital types in pediatric inpatient care. The mean rates and ABCs for SCD and mental health disorders were much higher and with more outlier hospitals, which indicate high‐value targets for quality improvement.